Drugs influencing on PCSK9 activity: modelling of efficacy in patients who had myocardial infarction with uncontrolled dyslipidemia - V. I. Ignatyeva; A. V. Kontsevaya; O. M. Drapkina; E. V. Derkach (Izdatelstvo OKI, 2023)
Cardiovascular diseases are the leading cause of death worldwide. It is possible to inﬂuence the development of these diseases by inﬂuencing their main pathogenetic link - dyslipidemia.Aim: to evaluate, using the example of alirocumab, the potential eﬀect of drugs aﬀecting the activity of PCSK9 on the achievement of goals for the prevention of the development of cardiovascular diseases and cardiovascular complications in patients of working age who had an acute myocardial infarction (MI) less than a year ago, with uncontrolled dyslipidemia.Materials and methods. The target group was created based on the Russian clinical guidelines; its number was calculated using Russian registry data. Based on the published results of the clinical trial of alirocumab ODYSSEY OUTCOMES in a group of patients with LDL cholesterol levels of more than 2.6 mmol/l (100 mg/dl), a model was built to estimate the number of fatal and non-fatal outcomes in the target group with standard therapy and with alirocumab.Results. The eﬀect of alirocumab administration was modeled in patients of working age who had a myocardial infarction less than 12 months ago with an LDL cholesterol level of more than 5.0 mmol/l, the number of this group in the Russian Federation was estimated to be 3,029 people. It has been shown that with therapy in this group, mortality can be reduced by 29%, and the number of non-fatal cardiovascular events - by 22%, i. e. alirocumab therapy in this group for 2 years can prevent 29 deaths and 185 non-fatal events, with an increase in the duration of therapy to 5 years, the number of lives saved will be 117 and 401 non-fatal cardiovascular events will be prevented.Conclusion. Modeling has shown that alirocumab therapy in patients with recent myocardial infarction and LDL cholesterol levels above 5.0 mmol/L will signiﬁcantly reduce mortality in this group and prevent the development of serious nonfatal cardiovascular complications, which will also reduce the burden on specialized hospitals, as well as prevent patients from becoming disabled. At the same time, decision making requires a balanced consideration of all ethical, clinical and economic aspects, including the assessment of costs and potential eﬀects from the position of the of a willingness to pay and the formation of the budget of the health system.